2014
DOI: 10.1111/tog.12145
|View full text |Cite
|
Sign up to set email alerts
|

The use of mifepristone and misoprostol in the management of late intrauterine fetal death

Abstract: Key content A combination of mifepristone and misoprostol is the gold standard treatment for induction of labour in women with late intrauterine fetal death. This article attempts to review the current best available evidence as well as provide an insight based on the available evidence regarding the dosing regimens and safety in women with a previous caesarean section. Learning objectives To review the pharmacokinetics, mode of action, efficacy, adverse effects, dose and route of administration of mifep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Based on the weeks of gestational age of onset (GAO), third trimester is defined as ≥27 weeks [ 10 ]. Term pregnancy is defined as delivery between 37 + 0 and 41 + 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the weeks of gestational age of onset (GAO), third trimester is defined as ≥27 weeks [ 10 ]. Term pregnancy is defined as delivery between 37 + 0 and 41 + 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Mifepristone (RU 486), a progesterone antagonist that increases the sensitivity of the myometrium to prostaglandins, has been used prior to misoprostol for mid‐trimester termination of pregnancy (TOP) in a few randomized trials with proven benefits . However, the evidence related to the use of the such a combination for the induction of labor in second and third trimester IUFD is deficient in the absence of well‐designed randomized controlled trials (RCT) . Of the seven available studies that used mifepristone‐misoprostol in cases of fetal death, four were retrospective and three, although prospective, lacked the quality of randomized trials …”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are similar to the findings in other reports. 10 In present study, women with IUFD and prior cesarean section, trial of labour following induction with EAS instillation and prostaglandins was found to be effective. 33 women were given trial of labour.…”
Section: Discussionmentioning
confidence: 52%